P210 The national lung cancer audit—year 5 completeness and outcomes. (16th November 2010) - Beckett, P; Woolhouse, I; Stanley, R; Peake, M D
Abstract : Introduction: The National Lung Cancer Audit aims to record outcomes in lung cancer on a large scale and through case-mix adjustment, start to explain the wide variations noted. Although Wales and Scotland also submit data to the audit, this abstract presents results for England only. Results: In Year 5, participation has again increased and the number of cases submitted has risen from 10 920 cases in 2005, to 16 922 in 2006, to 20 639 in 2007 to 25 757 in 2008, and to 30 155 in 2009. Completeness of data on individual cases has also improved—recording of PS has risen to 88%, stage to 80% and treatment to 89% of cases. Results suggest that the quality of care is improving, with annual increases in the proportion of patients being discussed in an MDT, proportion of patients receiving anti-cancer treatment, and in the surgical resection rate (see Abstract P210 Table 1 ). Data also show that the degree of variation across organisation is reducing year-on-year. Conclusions: These results once again highlight the considerable achievement of the National Lung Cancer Audit in collecting data and are a testament to the hard work of lung cancer teams across the country in achieving such high quality data on such a large scale. The results suggest that care for lung cancer patients is slowly improving, although some of the apparent improvement is likely to reflect the rise in data quality. However, wide variations in outcomes still persist between organisations, which need to be the focus of on-going service improvement work.